The relationship of accounting comparability between the profit value relevance and book value - Ojaghi, Sama; Moradi, Majid; Gorjizadeh, Davood (Technium Sustainability, 2021)
This research tries to investigate the comparability between the profit value relevance and book value of the listed firms in Tehran Stock Exchange. The research sample was selected by using the systematic removal sampling method by applying the research variable, 138 variables, during 2012-2019. Furthermore, this research has two hypotheses. This research is applied and the method is correlational based on nature and content. The research was conducted in the framework of deductive-inductive reasoning and panel analysis was used to analyze the hypotheses. The results of hypothesis testing showed that value relevance of profit and value relevance of book value increase with accounting comparability. Youtube link: https://youtu.be/lGbO2Co0Tyk